VALIDATION OF A NEW GLOBAL 30-MIN DRAINAGE DIRECTION MAP - Doll P.; Lehner B. (My University, 2002)
Digital drainage direction maps are a prerequisite for analyzing the flow of water on the land surface of the Earth. For continental or global studies, the most appropriate and most frequently used resolution for such data sets appears to be 30' (longitude-by-latitude). In this paper we present the new global drainage direction map DDM30, a 30' raster map of surface drainage directions, which organizes the Earth's land area into drainage basins and provides the river network topology. DDM30 was generated by first upscaling two drainage direction maps (DDMs) at higher resolutions. The resulting map was then extensively corrected in an iterative manner by comparison against vectorized, high resolution river maps and other geographic information. Finally, it was co-referenced to the locations of 935 gauging stations (provided by the Global Runoff Data Centre GRDC), which again involved manual corrections. DDM30 was validated against drainage basin areas from the literature, against the given upstream areas of the GRDC stations and, most importantly, against information from HYDRO1k, a data set based on a hydrologically corrected 1-km digital elevation model which is thought to afford the best information on surface drainage currently available at the global scale. In the course of the validation, the quality of DDM30 was compared to three other 30' DDMs. The validation results show that DDM30 provides a more accurate representation of drainage directions and river network topology than the other 30' DDMs.
Keywords: DRAINAGE NETWORKS; DRAINAGE BASINS; RIVERS; GLOBAL MAP; DISCHARGE